Comparative metatranscriptomic signatures of wood and paper feeding in the gut of the termite Reticulitermes flavipes (Isoptera: Rhinotermitidae). Issue 2 (7th January 2013) - Raychoudhury, R.; Sen, R.; Cai, Y.; Sun, Y.; Lietze, V.‐U.; Boucias, D. G.; Scharf, M. E.
Abstract Termites are highly eusocial insects that thrive on recalcitrant materials like wood and soil and thus play important roles in global carbon recycling and also in damaging wooden structures. Termites, such as Reticulitermes flavipes (Rhinotermitidae), owe their success to their ability to extract nutrients from lignocellulose (a major component of wood) with the help of gut‐dwelling symbionts. With the aim to gain new insights into this enzymatic process we provided R. flavipes with a complex lignocellulose (wood) or pure cellulose (paper) diet and followed the resulting differential gene expression on a custom oligonucleotide‐microarray platform. We identified a set of expressed sequence tags (ESTs) with differential abundance between the two diet treatments and demonstrated the source (host/symbiont) of these genes, providing novel information on termite nutritional symbiosis. Our results reveal: (1) the majority of responsive wood‐ and paper‐abundant ESTs are from host and symbionts, respectively; (2) distinct pathways are associated with lignocellulose and cellulose feeding in both host and symbionts; and (3) sets of diet‐responsive ESTs encode putative digestive and wood‐related detoxification enzymes. Thus, this study illuminates the dynamics of termite nutritional symbiosis and reveals a pool of genes as potential targets for termite control and functional studies of termite‐symbiont interactions.